Olfactory Disturbances as a Manifestation of Corona Virus - Uliana Listianingrum Pratiwi; Rina Lestari (Sean Institute, 2023)
Corona Virus is a contagious infectious disease caused by the SARS-CoV-2 Virus. Who reported Approximately 3,349 786 cases of Covid-19 Worldwide. Clinical manifestations of this disease are quite diverse depending on the patient's immune condition and other comorbid diseases. Among the manifestations that often arise are fever, cough, acute respiratory disorders and olfactory dysfunction, namely anosmia, hyposmia and dysgeusia. prevention of transmission of Covid -19, namely by wearing a mask, washing hands frequently, maintaining distance in crowds and carrying out vaccinations